2014
DOI: 10.1007/s13555-014-0041-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Thread Lift for Facial Rejuvenation: a Study Performed with Happy Lift™ Revitalizing

Abstract: IntroductionBarbed suture lifting is a minimally invasive surgical technique for facial rejuvenation. This study examined the efficacy and associated risks with this procedure, using a new synthetic, monofilament suspension thread named “Happy Lift™ Revitalizing” (Promoitalia International S.r.l, Naples, Italy).MethodsAll the patients had average aging signs and required a lifting of modest degree. A total of 37 thread lifts were performed over a 24-month period.ResultsIn the majority of patients (89%), the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
148
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(161 citation statements)
references
References 14 publications
9
148
2
2
Order By: Relevance
“…In a study carried out by Savoia et al, the results revealed that of 37 subjects investigated, 33 (89%) of the patients were satisfied with their surgery, of which 65% had an excellent level of satisfaction and 24% had a good level of satisfaction. The results of their research are in line with those of our research.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a study carried out by Savoia et al, the results revealed that of 37 subjects investigated, 33 (89%) of the patients were satisfied with their surgery, of which 65% had an excellent level of satisfaction and 24% had a good level of satisfaction. The results of their research are in line with those of our research.…”
Section: Discussionmentioning
confidence: 96%
“…This dermatochalasis of the facial and cervical soft tissues is the cause of distinctive aging signs of the face and neck. Some of these signs are as follows: loose facial skin, sagging cheeks, excess skin hanging from the lower jawline, excess fat in the neck, and platysmal bands visible in the neck . Among other facial aging signs, we can highlight the profile of the mandibular margin: The forehead has horizontal wrinkles, to which vertical ones are added in the glabellar area; the zygomatic, malar region (middle face) displays a downward sliding; the skin of the eyelids become flabby and protrudes in correspondence with the lower eyelids due to production of adipose bubbles; and the parcel of platysma disappears from the neck .…”
Section: Introductionmentioning
confidence: 99%
“…3 A number of procedures have been tried over the past few decades to improve the appearance of a slack face without surgery. 5,9 In this study, the authors analyzed a new absorbable lifting device using polydioxanone (PDO). 5 Since Sulamanidze proposed procedures for lifting and rejuvenating facial tissues by means of Aptos threads in 1998, various techniques have been introduced, including Woffles thread lifting, Waptos suture lifting, Isse unidirectional barbed threads lifting, and silhouette lifting.…”
mentioning
confidence: 99%
“…It finds several indications both in reconstructive surgery and esthetic surgery for the body remodeling (Sinno et al 2016;Kasem et al 2015). The technique consists in the withdrawal of a small quantity of fat tissue from a suitable anatomic area (abdomen, sides, thighs, knees) and the reimplantation of this tissue in another corporeal district in the same individual, so as to obtain a filling effect (Joyce et al 2015;Savoia et al 2014;Savoia et al 2013). Therefore, the adipose tissue is taken and reimplanted in security in the same patient setting up an autologous transplant.…”
Section: Introductionmentioning
confidence: 99%